2022
DOI: 10.26434/chemrxiv-2022-41gpv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Electrochemical Conditioning on Nickel-based Oxygen Evolution Electrocatalysts

Yoon Jun Son,
Seonwoo Kim,
Vanessa Leung
et al.

Abstract: Electrochemical conditioning via chronopotentiometry (CP) and cyclic voltammetry (CV) is essential for the activation of oxygen evolution reaction (OER) electrocatalysts. While many reports have activated OER electrocatalysts using either CP or CV, the inherent differences between these two electrochemical conditioning methods for the activation of OER electrocatalytic materials have yet to be explored. Here, we investigate the effects of CP and CV electrochemical conditioning on a Ni-based OER precatalyst and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Also note that the redox overpotential increases upon cycling for each catalyst, i.e., E p,a increases and E p,c decreases (Figure S18), which is also similar to the behaviour of other Ni-based OER catalysts. [11] This universal phenomenon can possibly be attributed to the sluggish redox kinetics resulting from the thickening reconstructed amor- [18] Ni 0.9 Fe 0.1 O x , [19a] NiFeMo. [19b] phous layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also note that the redox overpotential increases upon cycling for each catalyst, i.e., E p,a increases and E p,c decreases (Figure S18), which is also similar to the behaviour of other Ni-based OER catalysts. [11] This universal phenomenon can possibly be attributed to the sluggish redox kinetics resulting from the thickening reconstructed amor- [18] Ni 0.9 Fe 0.1 O x , [19a] NiFeMo. [19b] phous layer.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Similarly, Mullins et al reported a significant performance elevation for multiple Ni-based catalysts after electrochemical conditioning, which leads to different degrees of surface reconstruction. [11] In addition to catalytic activity, the redox behaviour of NiFe-based catalysts was also probed. Boettcher et al found that the Ni redox peak position shifts to higher potential and peak intensity decreases with higher Fe content, indicating that Fe can suppress Ni redox processes, which may also influence the reconstruction degree.…”
Section: Introductionmentioning
confidence: 99%